Basic Construction of Sharia Economic Law Based on Ushul Fiqh Asy-Syafi'i (Critical Analysis of the Book of Ar-Risalah) - Mugni Muhit; Jajang Herawan; Muhammad Yunus (International Journal Labs, 2023)
Imam Shafi'i was the first to have the latest ideas and ideas of his time regarding the method of extracting Islamic law (Takhrij al-Ahkam), which was systematically poured into a paper entitled Ar-Risalah (letter). This bookkeeping effort was in line with the development of Islamic science at that time. The development of this science occurred during the time of Harun Al-Rashid and culminated in the time of Al-Ma'mun. The birth of the book of Ar-Risalah was the initial phase of the development of ushul fiqh science as a scientific discipline. So this book became the main reference for USHUL experts in the later period in compiling similar works. In the book ar-Risalah, it is found that ash-Shafi'i does not mention the name of his book, and does not even give its own theme to a number of important studies that came to be known as ushul fiqh, he wrote in a broader framework, namely: Kehujjahan as-Sunnah. Ar-Risale is just a treatise written by ash-Shafi'i at the request of al-Mahdi. This Ar-Risale still contains material that is not actually ushul Fiqh, the discussion of ushul fiqh is concentrated on As-Sunnah, Ijma', and Qiya which are solely to deny istihsan. The style of thinking and the factors that intervene in the method of istinbat ash-Shafi'i are commensurate with his educational background, he is one of the Imams of Ahlu as-Sunnah wa al-Jama'ah, who in his fiqhiyyah branch sided with two groups, namely ahlu al-Hadith and ahlu ar-Ra'yi (tawasuth). These two capacities of moderate thinking are what make Ash-Syafi'i so beloved and accepted by the majority of the world's Muslims, especially in Indonesia.